2020
DOI: 10.2196/19009
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health, Risk Factors, and Social Media Use During the COVID-19 Epidemic and Cordon Sanitaire Among the Community and Health Professionals in Wuhan, China: Cross-Sectional Survey

Abstract: Background The mental health consequences of the coronavirus disease (COVID-19) pandemic, community-wide interventions, and social media use during a pandemic are unclear. The first and most draconian interventions have been implemented in Wuhan, China, and these countermeasures have been increasingly deployed by countries around the world. Objective The aim of this study was to examine risk factors, including the use of social media, for probable anxie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
401
6
28

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 413 publications
(465 citation statements)
references
References 16 publications
30
401
6
28
Order By: Relevance
“…Additionally, being female, a lover level of education, having achild, living in a crowded family, a duration of social media/TVexposure above 1 hour per day, participant or someone in thevicinity contracting COVID-19, having a comorbid disease or aprevious psychiatric diagnosis were found to be independent riskfactors associated with the increased PTS, anxiety and depressionin our total study population, in line with the previous reports (6,(13)(14)(15)(16)(17)(18)(19)(20).These ndings essentially emphasize a higher risk forcertain individuals for psychological distress during the pandemic,based on their pre-trauma features such as gender, education andpsychiatric or medical history, as well as features such as traumadirectness, personal victimization of the individual and closerelatives and the amount of exposure through TV and social media.Of concern, the latter two can become particularly fertile groundsfor anxiety-provoking information and disinformation during apandemic.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, being female, a lover level of education, having achild, living in a crowded family, a duration of social media/TVexposure above 1 hour per day, participant or someone in thevicinity contracting COVID-19, having a comorbid disease or aprevious psychiatric diagnosis were found to be independent riskfactors associated with the increased PTS, anxiety and depressionin our total study population, in line with the previous reports (6,(13)(14)(15)(16)(17)(18)(19)(20).These ndings essentially emphasize a higher risk forcertain individuals for psychological distress during the pandemic,based on their pre-trauma features such as gender, education andpsychiatric or medical history, as well as features such as traumadirectness, personal victimization of the individual and closerelatives and the amount of exposure through TV and social media.Of concern, the latter two can become particularly fertile groundsfor anxiety-provoking information and disinformation during apandemic.…”
Section: Discussionsupporting
confidence: 91%
“…More broadly, our findings align with a large body of literature that has linked social media usage with adverse mental health (Karim et al, 2020;Schønning et al, 2020;Sharma et al, 2020). This pattern has been observed both outside and inside the crisis context: for example, even in the current COVID-19 crisis, the frequency of social media usage has been found to predict depression symptoms (Ni et al, 2020). Our study extends the existing research by demonstrating that specific messaging activities (day-to-day exchanges on WhatsApp) is linked to well-being.…”
Section: Socio-emotional Vulnerabilitysupporting
confidence: 76%
“…14 With regards to social media, while some studies from China have linked the duration of social media exposure positively with higher risks of anxiety and depression during the COVID-19. 15,16 there is also evidence of it aiding government and health agencies by drawing attention towards public emergencies and as a mode of mass communication. 17 On the other hand in an analysis on misinformation on Twitter, Kouzy et al reported that 24.8% of the 673 tweets they analysed included misinformation and 17.4% included unverifiable information regarding the COVID-19.…”
Section: Discussionmentioning
confidence: 99%